2021
DOI: 10.3390/ijms22105330
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen-Like Protein 1 Modulates Sorafenib Resistance in Human Hepatocellular Carcinoma Cells

Abstract: Despite liver cancer being the second-leading cause of cancer-related death worldwide, few systemic drugs have been approved. Sorafenib, the first FDA-approved systemic drug for unresectable hepatocellular carcinoma (HCC), is limited by resistance. However, the precise mechanisms underlying this phenomenon are unknown. Since fibrinogen-like 1 (FGL1) is involved in HCC progression and upregulated after anticancer therapy, we investigated its role in regulating sorafenib resistance in HCC. FGL1 expression was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…A previous study has shown that the suppression of FGL1 inhibits the expression of caspase 3 and PARP1, thereby enhancing the inhibitory and apoptosis-inducing activities of gefitinib in the non-small cell lung cancer (NSCLC) cell line PC9/GR [27]. Similarly, Son et al [28] reported that sorafenib-induced anti-tumor effects were enhanced by knocking down FGL1. Interestingly, high expression levels of FGL1 are related to high densities of LAG-3 + cells, confirming that FGL1 is a highaffinity ligand for LAG-3 [29].…”
Section: Discussionmentioning
confidence: 93%
“…A previous study has shown that the suppression of FGL1 inhibits the expression of caspase 3 and PARP1, thereby enhancing the inhibitory and apoptosis-inducing activities of gefitinib in the non-small cell lung cancer (NSCLC) cell line PC9/GR [27]. Similarly, Son et al [28] reported that sorafenib-induced anti-tumor effects were enhanced by knocking down FGL1. Interestingly, high expression levels of FGL1 are related to high densities of LAG-3 + cells, confirming that FGL1 is a highaffinity ligand for LAG-3 [29].…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, the colony forming function and IC50 values were two- to three-fold higher in the low FGL1 expression group compared to those of the high FGL1 expression group. The specific mechanisms may involve the high expression of FGL1, which may influence MAPK and autophagy-related signaling, verified by FGL1 silencing ( 97 ). Anti-PD1/CTLA-4 therapy is an effective immunotherapy for the highly metastatic uveal melanoma.…”
Section: Clinical Application Of Lag3/fglmentioning
confidence: 99%
“… 29 The expression of FGL1 not only affects the regeneration of hepatocytes, but also regulates the growth and proliferation of tumor cells. 30 , 31 The research shows that FGL1 is the main inhibitory ligand of lymphocyte activation gene 3 (LAG-3), which can inhibit antigen-specific T cell responses through the interaction of FGL1/LAG-3. 32 Blockade of the inhibiting signal of FGL1/LAG-3 by knockout of FGL1 or function-blocking monoclonal antibody (mAb) can enhance T cell immunity in the tumor microenvironment and inhibit tumor growth.…”
Section: Introductionmentioning
confidence: 99%